2010
DOI: 10.1002/eat.20732
|View full text |Cite
|
Sign up to set email alerts
|

Association between serotonin transporter gene polymorphism and eating disorders: A meta‐analytic study

Abstract: These results suggested that the genetic variance of the serotonin transporter gene promoter contributed to the susceptibility of AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
3
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 46 publications
1
44
3
4
Order By: Relevance
“…This study has relevant strengths: in literature a number of review focusing on the genetic modulation of AN, 9 bulimia spectrum disorders, 10 and both AN, BN, and BED considered together 2 is present; moreover, two meta-analysis has been performed, the first on four article on AN 9 and the second on seven studies on AN and four on BN 11 ; however, to the best of our knowledge, our study is the first meta-analysis including AN, BN, and BED considered together and the meta-analysis including the largest number of studies on AN and BN separately. Moreover, as meta-analysis is a retrospective all-inclusive synthesis of published studies, type II errors are expected to be less common than in single studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has relevant strengths: in literature a number of review focusing on the genetic modulation of AN, 9 bulimia spectrum disorders, 10 and both AN, BN, and BED considered together 2 is present; moreover, two meta-analysis has been performed, the first on four article on AN 9 and the second on seven studies on AN and four on BN 11 ; however, to the best of our knowledge, our study is the first meta-analysis including AN, BN, and BED considered together and the meta-analysis including the largest number of studies on AN and BN separately. Moreover, as meta-analysis is a retrospective all-inclusive synthesis of published studies, type II errors are expected to be less common than in single studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of understanding the role of 5-HTTLPR polymorphism in eating disorders, a further meta-analysis was undertaken: (1) to investigate the association between 5-HTTLPR and eating disorders considered as a whole, including AN, BN, and BED studies; (2) to replicate results reported by Lee et al 11 on the association between 5-HTTLPR and AN and BN including in the analyses four further studies. Moreover, the quality of the included studies has been evaluated using the validated Newcastle-Ottawa Scale for case-control studies.…”
mentioning
confidence: 99%
“…In anorexia nervosa shared inheritance with depression (Strober et al 2000 ;Wade et al 2000), neurobiological, most notably serotonin dysfunction (Kaye et al 1998(Kaye et al , 2005 and concurrent depressive and obsessional psychopathology (Godart et al 2007 ;Kaye et al 2004) have suggested a role for antidepressant treatment. In addition a recent meta-analysis (Lee & Lin, 2010) has supported there being a specific genetic variant of the serotonin transporter gene promoter found in people with anorexia nervosa (but not bulimia nervosa). Similarly, there are high rates, up to 50 %, of lifetime comorbid depression and bulimia nervosa (Hudson et al 2007).…”
Section: Antidepressants and Like Medicationsmentioning
confidence: 93%
“…На выборке из 71 женщи-ны с ВЕD с ожирением и без такового (в группе контро-ля с нормальным весом была 61 женщина) показано, что не S-, а L-аллель 5-HTTLPR увеличивает риск раз-вития ВЕD [37]. Согласно результатам метаанализов, S-аллель 5-HTTLPR может являться фактором риска развития расстройств пищевого поведения в целом [38], особенно анорексии [28], для которой получены наи-лучшие показатели достоверности [39]. Однако доказа-тельств влияния на риск развития ВЕD до сих пор нет.…”
Section: молекулярная генетика веDunclassified